Pertanggungjawaban Kepala Sekolah Terhadap Perbuatan Korupsi Dana Bos - Sindy Tamara Putri; Budi Sastra Panjaitan (LPPM Universitas Ekasakti Padang, 2023)
The main factor in achieving maximum success in using BOS funds is how the school manages BOS funds. A good management system will help achieve the goals of the BOS funding program effectively and efficiently, which of course can improve the quality of education as expected. Corruption in the education sector is one of the most difficult forms of corruption to deal with. Corruption in the education sector is very dangerous, because it endangers the future of the country. The reason of this examination is to reveal the variables that driven Central SDN Kopa to commit the criminal act of debasement with regard to the School Administration Support, to find out what the legal sanctions are against a school principal who commits a criminal act of corruption against school operational aid funds, and how to analyze decision Number: 35 /Pid.Sus-TPK/2020/PN. Kpg. This sort of inquire about employments regulating lawful investigate with a case consider approach. The strategy utilized comprises of essential and auxiliary information utilizing subjective examination. The factors causing corruption in BOS funds carried out by unscrupulous school principals at the Kopa State Elementary School are the desire to make a profit, weak internal supervision, and the involvement of community supervision is still minimal.